Online social viewing: Cross-cultural adoption and uses of bullet-screen videos. Issue 3 (2nd July 2020) - Wan, Anan; Moscowitz, Leigh; Wu, Linwan
ABSTRACT: Bullet-screen technology, an innovative way of interacting with online videos, allows viewers to contribute comments that simultaneously appear over videos. Popular in East Asia, the technology is making its way to American audiences. This study employed a comparative qualitative focus group approach to explore how American and Chinese viewers responded to and interacted with this new format of online videos. Three themes emerge from this investigation: (1) the unique affordances of this technology; (2) barriers to adoption and usage; and (3) cultural differences that impact the user experience. The theoretical and practical implications for bullet-screen technologies are discussed.